Underestimated Passive Volcanic Sulfur Degassing Implies Overestimated Anthropogenic Aerosol Forcing. Issue 1 (6th January 2023) - Jongebloed, U. A.; Schauer, A. J.; Cole‐Dai, J.; Larrick, C. G.; Wood, R.; Fischer, T. P.; Carn, S. A.; Salimi, S.; Edouard, S. R.; Zhai, S.; Geng, L.; Alexander, B.
Abstract: The Arctic is warming at almost four times the global rate. An estimated sixty percent of greenhouse‐gas‐induced Arctic warming has been offset by anthropogenic aerosols, but the contribution of aerosols to radiative forcing (RF) represents the largest uncertainty in estimating total RF, largely due to unknown preindustrial aerosol abundance. Here, sulfur isotope measurements in a Greenland ice core show that passive volcanic degassing contributes up to 66 ± 10% of preindustrial ice core sulfate in years without major eruptions. A state‐of‐the‐art model indicates passive volcanic sulfur emissions influencing the Arctic are underestimated by up to a factor of three, possibly because many volcanic inventories do not include hydrogen sulfide emissions. Higher preindustrial volcanic sulfur emissions reduce modeled anthropogenic Arctic aerosol cooling by up to a factor of two (+0.11 to +0.29 W m −2 ), suggesting that underestimating passive volcanic sulfur emissions has significant implications for anthropogenic‐induced Arctic climate change. Plain Language Summary: Sulfate aerosols are particles in the atmosphere that have a net cooling effect on the climate. One of the most uncertain aspects of climate modeling is the abundance of sulfate aerosols during the preindustrial era. Without knowing the amount of sulfate aerosols during the preindustrial, it is difficult to estimate how much anthropogenic sulfate aerosols have offset warming from anthropogenic greenhouse gases. In this study, we examine preindustrial sulfate aerosols in a Greenland ice core. We find that sulfate aerosols from passive (i.e., non‐eruptive) volcanic degassing contribute almost two thirds of preindustrial Arctic sulfate aerosols in years without major volcanic eruptions. We compare this result to a state‐of‐the‐art global model and find that most climate models use a volcanic emissions inventory that underestimates preindustrial passive volcanic sulfur emissions. That volcanic inventory only includes one type of sulfur emission (sulfur dioxide), but studies have shown that volcanoes emit hydrogen sulfide, which can also form sulfate aerosols. We show that higher emissions of volcanic sulfur during the preindustrial era decrease the estimated cooling effect of anthropogenic aerosols during the industrial era. Thus, the underestimate of preindustrial volcanic emissions in current climate models has significant implications for anthropogenic climate change in the Arctic. Key Points: Sulfur isotopes in a Greenland ice core show that passive volcanic degassing contributes 66% of preindustrial Arctic sulfate The volcanic inventory used by most climate models underestimates passive degassing, possibly due to missing hydrogen sulfide emissions Elevated preindustrial passive volcanic degassing reduces the estimated cooling effect of anthropogenic sulfate in the Arctic